Prognostic Role of Long-Chain Acyl-Coenzyme A Synthetase Family Genes in Patients with Clear Cell Renal Cell Carcinoma: A Comprehensive Bioinformatics Analysis Confirmed with External Validation Cohorts - TEMİZ, MUSTAFA ZAFER; Colakerol, Aykut; Sönmez, Salih Zeki; Gökçe, Adem; Canitez, İbrahim Oğulcan; Özsoy, Şule; Kandıralı, Engin; Semerciöz, Atilla; Müslümanoğlu, Ahmet Yaser (CIG Media Group LP, 2023)
The prognostic role of long-chain acyl-CoA synthetases (ACSLs) was investigated using The Cancer Genome Atlas (TCGA) database for kidney clear cell carcinoma (KIRC) patients (n = 518). TCGA data were accessed via LinkedOmics database. We revealed lowered ACSL1 expression was associated with worse tumor histopathology and poor overall survival in ccRCC. It seems it may be used for prognostic marker for ccRCC. Introduction: We aimed to determine the prognostic role of long-chain acyl-CoA synthetases (ACSLs) as a disease marker for kidney clear cell carcinoma (KIRC). Patients and Methods: The Cancer Genome Atlas (TCGA) data were accessed via open access LinkedOmics database for KIRC. Provisional datasets were used for analysis as previously described and gene expression quantification data were downloaded. The corresponding clinical information of patients also were obtained from the database. Five ACSL family members, ACSL1, ACSL3, ACSL4, ACSL5, and ACSL6, were investigated in the TCGA-KIRC cohort. Xena browser, cBioPortal and UALCAN, and Cancer Cell Line Encyclopedia (CCLE) databases were also used to confirm the results. Exter nal validation was perfor med using patient cohorts from the Gene Expression Omnibus (GEO-NCBI) database. Finally, the protein-protein interaction (PPI) was constructed based on the Search Tool for the Retrieval of Interacting Genes (STRING) database and visualized using Cytoscape software. Results: Pathological T3-T4 stage tumors had significantly lower ACSL1 mRNA expression ( P = .009). Patients with pathologically confirmed metastasis exhibited significantly lower expression, as well ( P = .02). ACSL1 mRNA expression was associated with overall survival (OS) and negatively correlated with OS time. Univariate and multivariate analyses showed that lower ACSL1 mRNA expression level was associated with mortality. Moreover, ACSL1 mRNA expression was exhibited significant difference in some VHL gene region mutations and PBRM1_p.R1010 mutation, and negatively correlated with HIF1-alpha mRNA expression ( P < .001). Confirmatory analyses and external validation also revealed similar findings. Conclusion: Lowered ACSL1 mRNA expression is associated with worse tumor histopathology and poor overall survival in KIRC. It may be used for prognostic marker for KIRC.
Keywords: Kidney; Survival; Cancer; Long-Chain Acyl CoA; Gene Expression